1999
DOI: 10.1029/1999jd900080
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope composition of water vapor in the atmospheric boundary layer above the forests of New England

Abstract: paleoclimatology studies. This quantity, however, cannot be measured directly at the surface due to the instantaneous turbulent mixing of the evaporating water vapor with the overlying ABL. Using a 5 -1/Q mixing line method, we are able to determine such isotope flux ratios characterizing the two-way exchange between the Earth's surface and the free atmosphere. The varying isotope flux ratios are lighter than expected, but fall into the ranges of the isotope ratios of the winter precipitation in the area. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 27 publications
6
78
1
Order By: Relevance
“…This finding has since been supported by large-scale advection models that reproduce, to first order, the isotope ratios observed in the subtropical free troposphere near Hawaii [Galewsky et al, 2007;Hurley et al, 2012]. In addition, He and Smith [1999] characterized moisture transport between the land surface and free atmosphere by pairing measurements of humidity and the stable isotope ratio in a simple mixing model.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…This finding has since been supported by large-scale advection models that reproduce, to first order, the isotope ratios observed in the subtropical free troposphere near Hawaii [Galewsky et al, 2007;Hurley et al, 2012]. In addition, He and Smith [1999] characterized moisture transport between the land surface and free atmosphere by pairing measurements of humidity and the stable isotope ratio in a simple mixing model.…”
Section: Introductionmentioning
confidence: 71%
“…When conditions are unsaturated, both q and the isotope ratio are conserved variables, and airmass mixing will cause observations to fall along a line in δ-1/q space [e.g., He and Smith, 1999;Noone et al, 2011]. In contrast, if an air mass experiences a pseudoadiabatic process, in which condensate is immediately removed as precipitation, its δ value follows a theoretical Rayleigh distillation [e.g., Dansgaard, 1964].…”
Section: Isotopic Models For the Convective Boundary Layermentioning
confidence: 99%
See 1 more Smart Citation
“…As a rule of thumb, the δD of water vapor gradually decreases with altitude, which reflects the integrated history of condensation (e.g., Ehhalt et al 2005). While none of the previous observational studies have described the vertical profile of d-excess, calculated d-excess from isotopic profiles reported by He and Smith (1999) showed that the d-excess values at the top of a boundary layer are significantly higher than those at the surface. From these results, we can speculate that the δD (d-excess) values of water vapor impinging on the mountain region are lower (higher) than those for the marine air mass.…”
Section: Atmospheric Process Responsible For Warm Eventsmentioning
confidence: 96%
“…Note that the transpiration component of evapotranspiration is not expected to carry high d, as it has the same isotopic composition as the soil water at steady state (Yakir and Wang, 1996;Williams et al, 2004). In addition, the free atmospheric air is characterized by a isotopically lighter vapour (He and Smith, 1999;Bailey et al, 2013;Berkelhammer et al, 2013), and the dominance of entrainment during daytime is generally associated with a δ v depletion (Lai et al, 2006;Lai and Ehleringer, 2011;Tremoy et al, 2012;Bailey et al, 2013;Berkelhammer et al, 2013). Welp et al (2012) compared six measurement locations and found that both local evapotranspiration and entrainment were involved: in some of their sites, the d daily increase was associated with a δ 18 O decrease during the early morning due to entrainment of free atmosphere into the boundary layer during convective mixing, while the subsequent slight δ 18 O increase came from evapotranspiration.…”
Section: Daytime Processes: Contribution Of Local Evaporationmentioning
confidence: 99%